YTTRANDEFRIHET: Om rättigheter som politik och kulturell praktik - Dahre, Ulf Johansson (Tidsskriftet Antropologi, 2008)
The principle of free speech is considered fundamental for the democratic society. Free speech is a non-partisan principle that serves and favours no one. However, two recent controversial court cases in the Swedish Supreme Court show that the neutral free speech principle does not exist. The Supreme Court argued, in spite of the presumed neutrality of who says what, that it does matter who says what. The two cases concerned hate speeches against homosexuals. In the case against the speech of the church cleric, the court argued that freedom of religion is more fundamental than free speech and thus considered the disdain of homosexuals within the confi nes of the law. In the other case concerning the hate speech by a Nazi-nationalistic group, the same court argued that this was illegitimate speech. The speeches were similar in content. The conclusion from this might be that there is no such thing as free speech. The free speech arena is just a battlefi eld where different ideas and ideologies are competing for political and cultural hegemony in the state. Law, moreover, is an expression of the court’s defi nition of the cultural content in society.